2014
DOI: 10.5551/jat.21337
|View full text |Cite
|
Sign up to set email alerts
|

Declining Prevalence of Coronary Artery Disease in Incident Dialysis Patients Over the Past Two Decades

Abstract: Aim:The medical management of patients with chronic kidney disease (CKD) has changed within the past 20 years. We speculate that this change has resulted in a decrease in the prevalence of atherosclerotic cardiovascular disease in patients with CKD. The aim of the present study was to analyze changes in the prevalence of coronary artery disease (CAD) in patients newly started on hemodialysis, as well as trends in clinical factors and medications over the past two decades. Methods: This single-center cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Recently, Iwasaki et al examined the prevalence of coronary artery disease in incident dialysis patients over two decades and reported that the prevalence of unidentified coronary artery disease gradually declined from 69% to 25% over 18 years . These investigators also found a significant negative correlation between the prevalence of unidentified coronary artery disease and the ratio of ESA use.…”
Section: Cardiovascular Disease and Mortality At The Initiation Of Hamentioning
confidence: 99%
“…Recently, Iwasaki et al examined the prevalence of coronary artery disease in incident dialysis patients over two decades and reported that the prevalence of unidentified coronary artery disease gradually declined from 69% to 25% over 18 years . These investigators also found a significant negative correlation between the prevalence of unidentified coronary artery disease and the ratio of ESA use.…”
Section: Cardiovascular Disease and Mortality At The Initiation Of Hamentioning
confidence: 99%
“…Iwasaki et al [13] reported that the prevalence of CAD gradually declined from 69 to 25% over 18 years in hemodialysis patients, and the use of ESAs seemed to be associated with this decrease in CAD. Erythropoietin (Epo) and Epo receptor are expressed in a variety of tissues, including the vascular system [14].…”
Section: Discussionmentioning
confidence: 99%
“…The causality underscoring these differences is not well understood, although haemodialysis-specific syndromes such as intradialytic hypotension and myocardial stunning are contributors [ 22 , 23 ]. More recent data suggest that the aggressive management of traditional CV risk factors has led to a decline in the incidence of significant coronary artery disease [ 24 ].…”
Section: Clinical Manifestations Of Crsmentioning
confidence: 99%